The Analysis of Children’s Mathematical Giftedness through Snakes and Ladders Game at PAUD Sandhy Putra Telkom Ternate - Bahran Taib, Yahya Hairun, Susana R Bahara (International Journal of Advanced Science and Technology, 2020)
The title of this research is the analysis of Children’s Mathematical giftedness through the snakes and ladders game at PAUD Sandhy Putra Telkom Ternate. The aim of this research is to analyze how much the mathematical giftedness of children at PAUD Sandhy Putra Telkom Ternate. The study was conducted through observation by using observation instruments. The observation instrument contains a checklist of activities carried out by children, which is categorized as early childhood giftedness at PAUD Sandhy Putra Telkom Ternate. Furthermore, the results of the observation were analyzed qualitatively with the theoretical study of child development. The results of his research concluded that the application of this game model at PAUD Sandhy Putra Telkom was adjusted to develop the giftedness of students. One gifted development is mathematical giftedness of early childhood through the game of snakes and ladders. Basically, every child has different talents. The development of mathematical giftedness in early childhood should be done through the use of concrete objects and the habit of using mathematics in order that children can understand mathematics, such as counting, numbers, and mathematical operation. Children who have mathematical giftedness have the ability to think systematically, deductive and inductive, have more responsive to problems, and works sequentially or systematically. The research suggestions are that teachers must be more creative in creating new games or modifying existing games to suit the needs of the giftedness of early childhood. It is intended that students do not get bored with the monotonous game.